If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + y + 0 = 3 Reorder the terms: 0 + 5x + y = 3 Remove the zero: 5x + y = 3 Solving 5x + y = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 5x + y + -1y = 3 + -1y Combine like terms: y + -1y = 0 5x + 0 = 3 + -1y 5x = 3 + -1y Divide each side by '5'. x = 0.6 + -0.2y Simplifying x = 0.6 + -0.2y
| 1=-0.25n+1 | | 5x-3(x-3)=-17 | | (x-8)+(5x)=(9x-80) | | 14=5n+4+5n | | 7(x+5)+6(x-1)=-10 | | 3.9-30= | | X-4-20x=-2 | | 6x^2-4x-20=14 | | X+3*4= | | X^2+13x+36=36 | | 54=27x | | 2x-4+12=8(x+1-2x) | | 45/(4+1)=18-49*(3+2) | | 5x+y+3=3 | | 4t^2-4t-8=0 | | 2y+x=110fory | | c=5a+b | | 2(x+6)=4(x+2.6) | | x-.4=.4x | | 45/(4+1)= | | -4(5a-10)=0 | | f(x)=27x | | 60c-54c+108=0 | | 2x-4+12=8(x+1)-2x | | x^2+169-12=0 | | -5+7(x+6)=x+37 | | (x+2)4=8 | | 15x^2+16x+7=0 | | 33-(x+5)=8x-8 | | d=18+-27 | | (4b+3c)(5b+2c)=0 | | 200=2x+100 |